Spiritualitas Dan Proactive Coping Pada Survivor Bencana Gempa Bumi Di Bantul - Ardiman Adami; Rr Indah Ria Sulisyorini (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2008)
The purpose of this research is to find correlation between spirituality and proactive coping among survivors of Bantul earthquake. Hypotheses proposed is that there’s a positive correlation between spirituality and proactive coping among survivors.Subjects were 92 residence of Bantul and who were survive of earthquake on last May 27 2006. Scales for measurement were proactive coping inventory (Greenglass, 2002) and Spiritual Transedence Scale (Piedmont, 1999). Reliability of proactive inventory and spiritual transedence scale in order are 0.909 and 0.933.Data tested by Pearson’s correlation product moment via SPSS for windows. Result of the research showed that spirituality and proactive coping are having very significant correlation coefficients 0.741 (p=0.000). It mean that spirituality influence the emergence of proactive coping among earthquake survivor. Key words : spirituality, proactive coping, earthquake survive